Pelatihan Google Scholar Mahasiswa Cendekia di Pondok Pesantren Alif Lam Mim (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
One of the objectives of the National Science and Technology System is to increase the independence and competitiveness of the nation, meaning that universities are supported by research and development institutions (LPNK, LPK, and Business Entities) and qualified higher education personnel so that they can contribute to economic development and community welfare. One of the efforts made by Mahad Al-Jamiah IAIN Pekalongan to realize this goal is by increasing knowledge and skills to improve the quality of Scholar Students (students guided by Mahad Al-Jamiah IAIN Pekalongan), by holding a mentoring program in the field of research and writing. One of the activities is creating a Google Scholar account. The purpose of holding training to create a Google Scholar account is that scholar students are expected to be able to create a Google Scholar account which is used to support students' publications to be known by others. The method in this service uses a direct service method through practice in the form of training and mentoring in creating a Google Scholar account. The results of this service show that students can find out how to create a Google Scholar account. Then the method directed by the teaching lecturer is easy for students to understand because it provides systematic material. So that this activity can motivate students to be "technologically literate" and start to be enthusiastic about productively producing written works to be published on Google Scholar.